Cyanoacrylate Skin Surface Stripping and the 3S-Biokit Advent in Tropical Dermatology: A Look from Liège - Piérard, Gérald E. (Hindawi Publishing Corporation, 2014)
In the dermatopathology field, some simple available laboratory tests require minimum equipment for establishing a diagnosis. Among them, the cyanoacrylate skin surface stripping (CSSS), formerly named skin surface biopsy or follicular biopsy, represents a convenient low cost procedure. It is a minimally invasive method collecting a continuous sheet of stratum corneum and horny follicular casts. In the vast majority of cases, it is painless and is unassociated with adverse events. CSSS can be performed in subjects of any age. The method has a number of applications in diagnostic dermatopathology and cosmetology, as well as in experimental dermatology settings. A series of derived analytic procedures include xerosis grading, comedometry, corneofungimetry, corneodynamics of stratum corneum renewal, corneomelametry, corneosurfametry, and corneoxenometry.